2016
DOI: 10.1371/journal.pone.0161897
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Retinopathy in Patients with Diabetic Nephropathy: Development and Progression

Abstract: The purpose of current study aims to investigate the development and progression of diabetic retinopathy (DR) in patients with diabetic nephropathy (DN) in a nationwide population-based cohort in Taiwan. Newly diagnosed DN patients and age- and sex-matched controls were identified from the Taiwanese Longitudinal Health Insurance Database from 2000 to 2010. We studied the effects of age, sex, hypertension, dyslipidemia, diabetic polyneuropathy (DPN), and medications on the development of nonproliferative DR (NP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
51
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 79 publications
5
51
0
3
Order By: Relevance
“…The presence of microalbuminuria was found to independently increase the risk of DR, severe DR and DMO, and the risk further increased in the presence of macroalbuminuria . However, research has also shown that nephropathy did not affect development or progression of DMO, although it was an independent risk factor for DR, PDR and the progression from non‐proliferative DR (NPDR) to PDR . Previously, macroalbuminuria, but not microalbuminuria, had been found to be significantly associated with increasing severity of DR and with progression from NPDR to PDR in T2DM …”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…The presence of microalbuminuria was found to independently increase the risk of DR, severe DR and DMO, and the risk further increased in the presence of macroalbuminuria . However, research has also shown that nephropathy did not affect development or progression of DMO, although it was an independent risk factor for DR, PDR and the progression from non‐proliferative DR (NPDR) to PDR . Previously, macroalbuminuria, but not microalbuminuria, had been found to be significantly associated with increasing severity of DR and with progression from NPDR to PDR in T2DM …”
Section: Resultsmentioning
confidence: 98%
“…Although a previous study demonstrated that these two complications influence the incidence of each other, a retrospective study in T2DM demonstrated that the association between DR and diabetic nephropathy is unidirectional and that renal injury precedes retinal damage . Accordingly, several studies have shown that nephropathy is a risk factor for DR, including severe forms of retinopathy . Concerning T1DM, a 20‐year prospective study by Romero‐Aroca et al found that both micro‐ and macroalbuminuria correlated with the development of VTDR but not with the development of any DR .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1). We found that GG-homozygosity was significantly associated with DN in univariate modeling (p = 0.011) and in a multivariate model (OR 6.07 [1.60-22.99], p = 0.008) of clinical factors previously attributed to DN [14,15] (Table 2). Additionally, advanced stages of CKD were independently associated with DN (OR 1.93 [1.15-3.23], p = 0.012).…”
Section: Mmp-9 Rs17576 Snp In Association With Diabetic Nephropathymentioning
confidence: 83%